EFFECT OF VARIED KINDS OF SMOKE SOURCE MATERIAL ON THE QUALITY OF SMOKED CATFISH (Pangasius hypophthalmus) - Ahmad Arif; Sukirno Mus; Tjipto Leksono (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This research was conducted in December 2014. The purpose of this study was to determine effect of varied kinds of smoke source material on the quality of smoked catfish (pangasius hypophthalmus). There are three kinds of smoke source materials used for smoking catfish, namely: coconut shell and coconut husk, the mixture coconut shell and husk. The parameters used to measure the quality of the smoked catfish are sensory value, the content of total acid and total phenols, water content and pH value. The results showed that the use of different kinds of smoke source materials significantly affected to the appearance and taste value, total phenols, and the pH value, but did not significantly affect to the value of the texture and smell, moisture content and the content of total acids. The use of smoke source mixture of husk and coco shell is the best treatment, showed by the highest sensory value, those are consistence 7.6, texture 7.8, odor, 7.6 smell and taste 7.7. It means that the smoked fish is shiny and intact, has dense and compact texture, distinctive odor of smoked fish and have a good characteristic flavor of smoked fish. Catfish smoke contained total phenols 15.78 ppm, total acid 21.15 %, water content of 30%, and pH value 7.22.Keywords: Fish smoking, smoke source, catfish, coco husk and shell.